Application of numerical simulation for identification of Johnson-Cook material model parameters for aluminum under high-speed loading - Kuzkin, Vitaly Andreevich; Mihaluk, Dmitry Sergeevich (Computational Continuum Mechanics, 2010)
The problem of identification of the parameters of the Johnson-Cook material model with the Mie-Gruneisen equation of state (EOS) is studied. Finite element modeling of high-speed impact of two aluminum plates is carried out using the LS-DYNA code. The time-dependence of the free surface velocity of the target is obtained. The influence of material parameters (percussive adiabat slope, hardening, viscosity) on this dependence is investigated. The parameters are chosen so that they fit the known experimental data. Very good agreement between experimental and numerical results is achieved.